Tanggung Jawab Notaris atas Pembuatan Akta yang Kemudian Disengketakan oleh Ahli Waris (Studi Putusan Nomor 33/Pdt/2022/ Pt. Bdg) - Iin Hot Prinauli Purba; Sesuai Niandro Baeha (Verdict: Journal of Law Science, 2026)
This study analyzes the responsibility of a notary in the preparation of a land grant deed that subsequently becomes the subject of a dispute among heirs, with reference to Decision Number 33/PDT/2022/PT BDG. The research is motivated by the increasing number of inheritance disputes involving authentic grant deeds and the need to clarify the scope of notarial liability. This study employs normative legal research using statutory, case, and conceptual approaches. Primary legal materials include relevant legislation and court decisions, while secondary materials consist of legal literature and scholarly publications. The collected materials are analyzed qualitatively through legal interpretation and examination of the judges’ reasoning. The findings demonstrate that a notary’s responsibility may arise under civil, administrative, or criminal law, depending on the existence of fault or negligence. Civil liability may be imposed if a notary commits an unlawful act causing loss to the parties. Administrative sanctions may be imposed for violations of statutory duties under the Law on Notary Office, whereas criminal liability arises only when intentional misconduct, such as forgery or deliberate inclusion of false information, is proven. In Decision Number 33/PDT/2022/PT BDG, the court held that the repeated filing of lawsuits by the defendant did not constitute an unlawful act because access to the courts is a legally protected right. The grant deed was not declared invalid or annulled, and no evidence established that the notary had violated legal procedures in preparing the deed. Consequently, the notary could not be held liable. The study concludes that notarial liability is based on proven fault rather than the mere existence of a dispute concerning an authentic deed.